Human Capital Accounting: A Literature Review Of Valuation, Disclosure, and Organizational Impact - Prasetia, Dimas; Maisarah, Sausan Nuhaa (DAS Institute, 2025)
This study conducts a systematic literature review to explore the development of Human Capital Accounting (HCA) in the last decade, focusing on three primary areas: valuation approaches, disclosure practices, and organizational impact. A total of 21 articles were selected using the PRISMA protocol from reputable databases. The analysis reveals that no single method dominates the valuation of human capital. Instead, multiple frameworks—such as cost-based, income-based, and efficiency-based models—are applied, often in combination. The Value Added Intellectual Coefficient (VAIC) model and Data Envelopment Analysis (DEA) have gained traction as practical tools for measuring human capital efficiency. In terms of disclosure, voluntary reporting of human capital information is increasing, though inconsistencies remain across firms and sectors. Enhanced disclosure practices are positively associated with firm value and stakeholder confidence, especially in integrated reporting contexts. Finally, the organizational impact of HCA is evident in improved financial performance, productivity, and strategic decision-making, particularly when human capital is integrated with broader organizational planning. The study concludes that while the field remains fragmented, there is a growing consensus on the critical role of human capital in value creation. Future research should focus on standardizing measurement and reporting practices to strengthen the strategic role of HCA in corporate governance and sustainability.